Comparison of Rhenium-188, Rhenium-186-HEDP and Strontium-89 in palliation of painful bone metastases - Liepe, K.; Franke, W.-G-; Kropp, J.; Koch, R.; Runge, R.; Hliscs, R. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: Several radiopharmaceuticals were compared previously with regard to the efficiency in pain palliation of bone metastases. Furthermore, first results were reported on the suitability for such kind of therapy of the generator produced radionuclide rhenium-188. Method: Influence of Rhenium-188-HEDP (Re-188), Rhenium-186-HEDP (Re-186) and Strontium-89 (Sr-89) on pain symptoms and bone marrow function were obtained in 44 patients (pts). These were 16 pts. with Re-188 (2943 ± 609 MBq), 13 pts. with Re-186 (1341 ± 161 MBq) and 15 pts. with Sr-89 (152 ±18 MBq) (6 woman with breast cancer and 38 mens with prostata cancer). Results: 81 of pts. after Re-188,77% after Re-186 and 80 % after Sr-89 reported relief of pain. The Karnofsky-lndex established by pts. increased from 74 ± 9% to 85 ± 11 % after Re-188, from 70 ± 1 1 % to 76 ± 1 1 % after Re-186 and from 62 ± 10% to 69 ± 10% after Sr-89. However, the difference between the pre- and the post-therapeutic value is only statistically significant in the case of Re-188 therapy (p = 0.001 ). A decrease of platelets of 30 ± 14% after 2.8 ± 0.7 for pts. treated with Re-188, of 39 ± 20% after 3.7 ± 1.0 weeks for pts. treated with Re-186 and of 34 ± 26% after 4.4 ± 1.0 weeks for pts. treated with Sr-89 compared to the value before therapy was observed. The difference was not significant between the 3 groups of pts. (p= 0.125 to 0.862). Conclusion: All tried radiopharmaceuticals were effective in pain palliation. The various radionuclides had no significant difference in the pain relief or the bone marrow impairment. If only the Karnofsky-lndex after Re-188 HEDP seems to be a little more increase.
Keywords: Rhenium-188-HEDP; Rhenium-186-HEDP; Strontium-89; pain palliation; bone metastases